Sustaining inclusive-multicultural education: Islamic religious education practices in a junior secondary school - Maimunah Maimunah; Siti Nur Syamimi Binti Adam Malik (ATTARBIYAH: Journal of Islamic Culture and Education, 2026)
Many studies have discussed inclusive multicultural education from global and national perspectives, yet limited research examines its concrete implementation in Islamic Religious Education (IRE) at the junior secondary level, a crucial stage for identity formation and social interaction. This study analyzes the implementation of inclusive multicultural education in IRE learning at State Junior High School 2 South Pontianak and examines its sustainability using Talcott Parsons' social system theory. Employing a qualitative descriptive approach, data were collected through interviews, observations, and documentation. The findings show that inclusive multicultural practices are systematically implemented through four main principles: equity and quality improvement, recognition of diversity, meaningful learning, and stakeholder engagement. The sustainability of this model is reflected in its fulfillment of Parsons' four social system functions: adaptation, goal attainment, integration, and pattern maintenance. The study demonstrates that IRE functions not only as religious instruction but also as a social mechanism for fostering inclusive and multicultural values within the school environment. The integration of moral, social, and spiritual dimensions creates an educational system that is participatory, just, and civilized. Conceptually, this research contributes to the development of inclusive and multicultural Islamic education practices and offers an adaptable model for broader educational contexts in Indonesia.